An explanatory sequential investigation of the working alliance as a change process in videoconferencing psychotherapy - Norwood, Carl (2019)
Background – The remote delivery of psychotherapy via secure video link— videoconferencing psychotherapy (VCP)— has the potential to overcome many of the regularly cited barriers to accessing psychological treatment and is becoming more recognised as a means of increasing access to services. Despite this, relatively little empirical investigation has been conducted examining the working alliance as a change process through this medium, and debate exists as to the experiential nature of the working alliance when therapy is delivered through this medium.